A study of the mechanisms of transmission of respiratory-tract pathogenic bacteria - Duguid, J. P. (The University of Edinburgh, 1949)
Pulmonary tuberculosis is contracted mainly by inhalation into the lungs of small airborne infected dust -particles liberated from handkerchiefs, clothes, bedding and carpets which have been soiled by the sputum or by the large projectile cough- droplets of ' patients. A much less important, but possibly not rare, mode of infection is by inhalation of small infected droplet- nuclei introduced into the air by the coughing of patients. A third, and probably rare, mode of infection is by ingestion into the mouth, on fingers or eating utensils, of tubercle bacilli acquired from patients by contact, with subsequent aspiration of the bacilli, probably in small droplets of saliva, from mouth to lungs via the trachea. Tubercle bacilli acquired by ingestion, and invading the body through the tonsils or intestines, do not give rise to pulmonary tuberculosis apart from military lung infection due to haematogenous spread from a primary alimentary-tract lesion.